2020
DOI: 10.1101/2020.11.11.20227777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic blockade of Clever-1 elicits lymphocyte activation alongside checkpoint molecule downregulation in patients with solid tumors

Abstract: Macrophages are critical in driving an immunosuppressive tumor microenvironment that counteracts the efficacy of T-cell targeting therapies. Thus, agents that can reprogram macrophages towards a proinflammatory state hold promise as novel immunotherapies for solid cancers. Here, we report that immunotherapeutic targeting of the macrophage scavenger receptor Clever-1 in heavily pretreated metastatic cancer patients was able to induce a significant increase and activation of peripheral T-cells. Anti-Clever-1 (FP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Interestingly, early results in patients where biopsies were undertaken did show a reduction of antiinflammatory intratumoral stabilin-1 þ macrophages and an increase in proinflammatory/adaptive immune cell subsets in selected patients. 176 This trial is ongoing and overall therapeutic efficacy is awaited, yet the data are consistent with the detrimental effects of TAM scavenger receptors and their role in driving an immunosuppressive TME, and also highlight therapeutic potential for their targeting within the context of HCC.…”
Section: Scavenger Receptors In Tamsmentioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, early results in patients where biopsies were undertaken did show a reduction of antiinflammatory intratumoral stabilin-1 þ macrophages and an increase in proinflammatory/adaptive immune cell subsets in selected patients. 176 This trial is ongoing and overall therapeutic efficacy is awaited, yet the data are consistent with the detrimental effects of TAM scavenger receptors and their role in driving an immunosuppressive TME, and also highlight therapeutic potential for their targeting within the context of HCC.…”
Section: Scavenger Receptors In Tamsmentioning
confidence: 76%
“…The first of these targeted scavenger receptor SCARB-1 in HCV cell entry in the context of liver transplantation 127 and the second is an early-phase clinical trial currently underway, targeting the scavenger receptor stabilin-1 on TAMs in solid tumors, including HCC. 176 In addition, scavenger receptors have also been explored as biomarkers of disease states, and here we highlight their potential as biomarkers in different etiologies of liver disease (►Fig. 2).…”
Section: Clinical Translation and Future Perspectivesmentioning
confidence: 99%
“…Stabilin-1 performs endocytosis, phagocytosis, intracellular sorting of newly synthetized proteins and transcytosis of growth hormone family member placental lactogen (9,(139)(140)(141)(142)(143)(144). Large body of evidence demonstrated that stabilin-1/CLEVER-1 can mediate cell-matrix and cell-cell interactions during primary tumor growth and in metastatic state (135,138,(145)(146)(147).…”
Section: Sr-h1/stabilin-1mentioning
confidence: 99%
“…As TGFBI and POSTN constitute paralogs it seems probable that both proteins contribute in certain diseases (Schwanekamp et al, 2016). Stab1 and Stab2 single inhibition mediates beneficial effects in atherosclerosis development (Manta et al, 2022), anti-Stab1 inhibition is in clinical trials in immuneoncology (Virtakoivu et al, 2021). We here assess the possible side effects of single and double Stabilin deficiency or inhibition on the scavenging of POSTN and TGFBI from the circulation and their tissue distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that Stab1/Stab2-double-knockout mice (Stab-DKO) present an impaired kidney function and a decreased lifespan likely due to their impaired scavenging function through LSECs (Schledzewski et al, 2011). Only recently, we were able to show that single Stabilin inhibition reduces atherosclerosis development (Manta et al, 2022), furthermore, anti-Stab1 antibodies are in initial clinical trials as an immunomodulatory cancer treatment (Virtakoivu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%